Tailoring zeolites for enhanced post-combustion CO2 capture: A critical review - Ali H. Whaieb; Farah T. Jasim; Amer A. Abdulrahman; Idres M. Khuder; Saba A. Gheni; Islam Md Rizwanul Fattah; Nalan Turkoz Karakullukcu (Current Research in Green and Sustainable Chemistry)
Fossil combustion mainly contributes to global warming and increases atmospheric CO2 levels, an essential greenhouse gas and environmental risk. The atmospheric CO2 level increased, emphasizing the necessity to restrict the emission while maintaining it out of the carbon cycle. Various porous adsorbents were created as CO2 capture sorbents, but they have been just moderately successful and require upgrading with more efficient porous adsorbents to address global climate issues caused by CO2. Due to their tunable pore sizes, high chemical stability, superior adsorption selectivity, and large surface area, zeolite-based adsorbents are considered promising materials for CO2 capture. Their framework structures allow for molecular sieving, ion exchange, and surface modifications, further enhancing their adsorption efficiency and regeneration capability.